Analysis and critical review of ICH Q8, Q9 and Q10 from a generic pharmaceutical industry view point - Ljuba Karanakov; Jasmina Tonic-Ribarska; Marija Glavas-Dodov; Suzana Trajkovic-Jolevska (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2012)
Generic industry aims to produce safe, efficient, built-in quality medicines that will satisfy patients' requirements and will be competitive on the market. In this paper, assessment of the need for quality by design (QbD) and process analytical technology (PAT) implementation by generic industry was made, by analysis of the ICH Q8, Q9 and Q10 guidelines and their implementation in European regulation. The review of the guidelines indicates differences in the life cycle of a generic medicine, leading to a final conclusion in terms of generic industry. PAT provides statistical analysis and real time quality monitoring, as the basis for proactive quality management. Using QbD/PAT, quality is proved and improved throughout the entire life cycle. Better understanding of the product and processes within a defined design space leads to easier proof of built-in quality throughout the life cycle of the medicine, faster and easier regulatory evaluation, faster time to market, as well as post marketing savings regarding costs and time. Implementation of QbD/PAT as a systematic approach together with risk assessment as part of quality management system is a useful challenge to the generic industry and gives an opportunity for technological, temporal, financial and quality improvement. It was concluded that having in mind its' own manufacturing capabilities the applicant should optimize the implementation of QbD in accordance with current good manufacturing practice guidelines. Implementation of QbD/PAT is an innovative challenge for the generic industry. Managing pharmaceutical quality system allows the top management to make right decisions at the right time.